Enhancing Mediation Skills through Legal Counseling for Indonesian Citizens in Thailand: A Case Study of PCIM Thailand: Peningkatan Keterampilan Mediasi melalui Penyuluhan Hukum bagi Warga Negara Indonesia di Thailand: Studi Kasus pada PCIM Thailand - Tinuk Dwi Cahyani; Saputra, Fauzan (Universitas Muhammadiyah Malang, 2025)
The objective of mediator legal counseling is to facilitate the resolution of legal issues encountered by Indonesian citizens and cadres residing in Thailand. However, PCIM Thailand lacks specialized expertise in out-of-court settlement or mediation. In this context, mediation is employed to reconcile disparities in bargaining power between conflicting parties to reach an agreement. The mediator's role is primarily focused on addressing the issues articulated by the conflicting parties. The counseling approach encompasses preparation, elucidation of the mediator's role and function, task allocation, and a question-and-answer session. All participants in this program observed a mediation simulation conducted by each group. Each group assumed the role of mediator and facilitated communication between both parties to resolve the dispute. The concept of